Preparedness of clinical supervisors to supervise podiatry students in Australia: A qualitative study - Katrina Reynolds; Michelle McLean (Bond University, 2022)
Clinical supervision is critical for preparing podiatry students for clinical practice. However, little is known about clinical supervisors' preparedness to supervise podiatry students in clinical practice. This exploratory qualitative study explored clinical supervisors' perceptions of their preparedness to supervise podiatry students in Australia, in terms of their training, challenges and suggestions for improving supervision quality. Semi-structured interviews with 11 clinical supervisors (6 females, 5 males) were audio-recorded, transcribed and thematically analysed. Watkins' (1990) four-stage model characterising supervisor development was used to inform analysis. Generally, clinical supervisors did not feel adequately prepared for their supervisory role, largely because of a lack of formal training. Challenges included the time burden of supervision, inconsistency regarding competence assessment standards, and student-related issues such as a perceived lack of interest. Recommendations for improving clinical supervision included a greater understanding of students' learning needs and more training opportunities. Clinical supervisors were of the opinion that partnering universities were largely responsible for ensuring quality supervision practices. As clinical supervisors generally felt unprepared to supervise, this impacted on their self-efficacy. Greater role clarity, training and support is thus needed to ensure clinical supervisors are adequately prepared for the role and to facilitate progression through supervisory developmental stages.